Is Our Water Affordable?. Issue 7 (1st July 2014) - Davis, Jon; Crea, Joe
Abstract : During the first decade of the 21st century, local governments spent nearly $1 trillion on capital investments for water and wastewater infrastructure. The anticipated need during the next 25 years is projected to match this amount for drinking water alone, whereas the wastewater investment is projected to be even greater. These are staggering amounts, especially when considering that this investment will be passed on to rate payers as grant funding is no longer an option for most utilities. Reliable access to water and wastewater service is a critical component of every society; however, providing that access is becoming a contentious issue.